Application of topology optimization technique in sand casting process of a complex product based on FDM 3D printing technology - Nguyen Huu Tho; Nguyen K. Dien; Trinh T. Tho; Nguyen V. Thanh; Nguyen V. A. Duy (Jurnal POLIMESIN, 2021)
Design optimization is one of the emerging CAE technologies thanks to the robust and strong structure of the computer and the ability to create complex designs using material additive technology. Recent modern innovations in 3D printing technology have made metal casting new breakthroughs. The demand of many products with complex shapes and geometries becomes very high. This makes the 3D printing more helpful and meaningful to contribute in the field of product design and development. This study presents an integrated framework for the implementation of complex 3D product design from fundamental technologies of CAD/CAE/AM (Computer Aided Design/Computer Aided Engineering/Additive manufacturing). Then, we apply casting technology to create models for products with complex shapes from FDM 3D printing technology. This integrated process is essential in assisting engineers to quickly design and create prototypes, and to fully control errors occurring during prototyping through CAD/CAE simulation to improve production efficiency of businesses and reduce time to bring products to customers. The experiment of sand casting based on the mold core from AM technology confirmed that the integrated approach is effective and applicable in the practice at manufacturing enterprises.